Thyroid Metastases from Hepatocellular Carcinoma after Liver Transplantation - Viana, Danilo Dias Avancini (2024)
Hepatocellular carcinoma (HCC) patients with metastases to the thyroid are extremely rare. A patient who underwent liver transplantation for HCC recurrence had metastatic thyroid recurrence detected 4 years later. A literature review identified six documented cases, analyzing relevant data on HCC with thyroid metastasis following liver transplantation. There is a prevalence of hepatitis B virus (HBV) and hepatitis C virus (HCV) as etiologies of liver disease (83.3%), with alpha-fetoprotein (AFP) levels elevated in five cases. Additionally, the time between the diagnosis of HCC and thyroid metastasis was within 3 years. The patient remains clinically stable in outpatient follow-up, with an 8-month current survival after total thyroidectomy.